Cases of mortality in little penguins (Eudyptula minor) in New Zealand associated with avian malaria. Issue 6 (2nd November 2017) - Sijbranda, DC; Hunter, S; Howe, L; Lenting, B; Argilla, L; Gartrell, BD
Abstract: CASE HISTORY: A little penguin ( Eudyptula minor ) of wild origin, in captivity at Wellington Zoo, became inappetent and lethargic in March 2013. Despite supportive care in the zoo's wildlife hospital, the bird died within 24 hours. CLINICAL FINDINGS: Weight loss, dehydration, pale mucous membranes, weakness, increased respiratory effort and biliverdinuria were apparent on physical examination. Microscopic evaluation of blood smears revealed intra-erythrocytic stages of Plasmodium spp. and a regenerative reticulocytosis in the absence of anaemia. PATHOLOGICAL FINDINGS: Post-mortem findings included reduced body condition, dehydration, pulmonary congestion and oedema, hepatomegaly, splenomegaly, hydropericardium and subcutaneous oedema. Histopathological findings included protozoal organisms in sections of lung, liver and spleen. A marked, diffuse, sub-acute interstitial histiocytic pneumonia was present. Accumulation of haemosiderin was noted in the Kupffer cells of the liver and in histiocytic-type cells in the spleen. MOLECULAR TESTING: DNA was extracted from frozen portions of the liver. Nested PCR results and DNA sequencing confirmed infection of the deceased little penguin with Plasmodium ( Huffia ) elongatum lineage GRW06. DIAGNOSIS: Avian malaria due to Plasmodium ( Huffia ) elongatum GRW06 RETROSPECTIVE INVESTIGATION: A retrospective analysis of 294 little penguin cases in the Massey University post-mortem database revealed three other potential avian malaria cases. Analysis of archived tissues using a nested PCR for Plasmodium spp. followed by DNA sequencing revealed that a little penguin which died at Auckland Zoo was infected with P. elongatum GRW06 and two wild little penguins found dead on New Zealand beaches were infected with P. relictum SGS1 and Plasmodium . sp. lineage LINN1. Therefore, the overall frequency of deaths in little penguins associated with avian malaria was 4/295 (1.36%). CLINICAL RELEVANCE: Our results suggest that avian malaria is associated with sporadic mortality in New Zealand's little penguins both in the wild and in captivity, but there is no evidence of mass mortality events due to Plasmodium spp. infection.